An outcome-based educational intervention to improve nursing students' knowledge and competencies in oncology nursing: a randomized controlled Trial. Issue 4 (3rd September 2019) - Hsu, Li-Ling; Ueng, Ruey-Shiuan; Hsieh, Suh-Ing
Abstract : Background : Caring for cancer patients is a complex process that requires considerable knowledge and a wide range of skills. Aim : The purpose of this study is to demonstrate that outcome-based course design would bring about significant differences in the nursing students' knowledge, confidence, and skills. Method : This was a randomized controlled trial with two-group pretest and post-test experimental study in 2014 involving a total of 213 students. The descriptive and inferential statistics were used to analyze the data. Results : The mean cancer nursing knowledge test score of the experimental group was higher than the control group at the post-test. The mean cognitive load score of the experimental group was lower than the control group at the post-test. The mean learning satisfaction and self-confidence score of the experimental group was higher than the control group. Conclusions : This study demonstrated the feasibility of implementing an outcome-based educational intervention in baccalaureate nursing education.